Development of flipped learning model learning assisted with spada learning management system - Sri Satriani; Wahyuddin; Agustan Syamsuddin (Postgraduate, University of Mataram, 2023)
This research aims to develop flipped learning model learning tools in Advanced Calculus courses through Online Learning Systems (SPADA). This research is development research with the research subjects being 26 Mathematics Education students. The learning tools developed were in the form of teaching materials and learning videos were validated by two material expert validators and two media expert validators. The research instruments used were teaching material validation sheets, learning video validation sheets, teaching material readability test sheets and student response questionnaires to learning videos. The results of the validation show that the learning tools developed are in the valid category and the student response questionnaire to the learning tools developed shows a good response, so it can be concluded that the learning tools developed in the form of textbooks and learning videos using the Flipped Learning model assisted by the SPADA Learning Management System have met validity, practicality, and effectiveness so that they can be used in the learning process.